2005
DOI: 10.1111/j.1439-0388.2005.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of properdin (BF) genotypes associated with litter size in a commercial pig cross population

Abstract: Properdin (BF) was investigated as a candidate gene influencing litter size in a commercial pig cross population. The BF gene was chosen because of its integral role in influencing uterine epithelium growth and because several quantitative trait loci (QTL) with impact on reproductive traits have been detected near the centromere of porcine chromosome 7. A total of 123 F2 (Large White x Landrace) x Leicoma sows were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
0
14
2
1
Order By: Relevance
“…The study showed a higher frequency of allele T (0.68) compared with allele C (0.32), which resulted in a relatively high frequency of the TT genotype (0.44) compared with the second homozygous genotype CC (0.14), while the heterozygous genotype TC had a frequency of 0.37. In a study by Buske et al [2], in commercial crossbred sows, the frequency of the T allele was much higher (0.89) than the allele C (0.11). They observed the highest frequency of TT genotype (0.81), which was much higher than TC (0.16) and individuals with the CC genotype (0.03).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study showed a higher frequency of allele T (0.68) compared with allele C (0.32), which resulted in a relatively high frequency of the TT genotype (0.44) compared with the second homozygous genotype CC (0.14), while the heterozygous genotype TC had a frequency of 0.37. In a study by Buske et al [2], in commercial crossbred sows, the frequency of the T allele was much higher (0.89) than the allele C (0.11). They observed the highest frequency of TT genotype (0.81), which was much higher than TC (0.16) and individuals with the CC genotype (0.03).…”
Section: Resultsmentioning
confidence: 99%
“…CC sows weaned the lowest number of piglets in the fi rst (p<0.01), second and third litter, but the difference was not signifi cant. Buske et al [2], showed signifi cant differences (p<0.05) of litter size against individual genotypes of the BF gene. The highest total number of piglets born and born alive in TT sows, the lowest in CC sows, and intermediate in TC sows.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations